Efficacy Sources that Predict Leadership Behaviors in Coaches of Athletes with Disabilities - Judge, Lawrence W. (J Hum Kinet, 2021)
Researchers suggest that sport participation among athletes with disabilities promotes healthier lifestyles, increases self-esteem, and enhances peer acceptance. Ideally, coaches should be confident in teaching skills, tactics, and sportsmanship, while exhibiting appropriate leadership behaviors in order to positively impact the psychosocial development of any athlete. Thus, the present research examined sources of coaching efficacy that predict leadership behaviors in coaches who work with athletes who have physical disabilities. Seventy international Paralympic coaches of female and male sport teams completed a modified version of the Coaching Success Questionnaire-2, the Coaching Efficacy Scale and the Leadership Scale for Sports. Regression models indicated that total coaching efficacy was a significant predictor of instructional and positive feedback leadership behaviors, with prior success also being a significant predictor of instructional behavior.